1991
DOI: 10.1049/el:19911276
|View full text |Cite|
|
Sign up to set email alerts
|

Current-mode oscillators using single current follower

Abstract: References prediction* from the above cited parameters and an assumed amplifier excess spontaneous emission factor of 1.4.We report two sets of BER measurements in Fig. 2. The first, carried out with the loop exactly as described above, and , , ' -1 0 1:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 0 publications
0
34
0
Order By: Relevance
“…Also, the condition of oscillation can be independently tuned by varying 3 . In addition, it can be shown that the output voltages (V 1 and V 2 ) and currents (I 1 and I 2 ) are in quadrature and will have equal amplitudes when C 1 = C 2 , R 1 = R 2 and 1 = 2 .…”
Section: Simulated Active Inductor-based Oscillatormentioning
confidence: 99%
See 3 more Smart Citations
“…Also, the condition of oscillation can be independently tuned by varying 3 . In addition, it can be shown that the output voltages (V 1 and V 2 ) and currents (I 1 and I 2 ) are in quadrature and will have equal amplitudes when C 1 = C 2 , R 1 = R 2 and 1 = 2 .…”
Section: Simulated Active Inductor-based Oscillatormentioning
confidence: 99%
“…Sinusoidal oscillator designs using the current-mode (CM) approach have gained considerable attention. Among these circuits, oscillators based on current followers (CFs) and/or voltage followers (VFs) such as those of [2][3][4][5][6][7] seem to be attractive. This stems from the high-frequency operation and low power consumption of the unity gain cells [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sinusoidal oscillators find numerous applications in communication, control systems, signal processing, instrumentation, and measurement systems; see [3][4][5] and the references cited therein. Explicit current-mode sinusoidal oscillators (ECMSOs) based upon different active single building blocks are available in the literature; see [6][7][8][9][10][11][12][13] and the references cited therein.…”
Section: Introductionmentioning
confidence: 99%